Neutralizing Unethical Negotiating Tactics: An Empirical Investigation of Approach Selection and Effectiveness. Issue 1 (January 2014) - Fleck, Denise; Volkema, Roger; Pereira, Sergio; Levy, Barbara; Vaccari, Lara
<x xml:space="preserve">Abstract</x> Negotiation is integral to business success, and information is the lifeblood of the negotiation process. When invalid information is disseminated via manipulation or deceit, one or more parties can suffer. Nonetheless, many studies have shown that the use of questionable or unethical tactics is commonplace. This article reports on a study of twelve behaviors that can neutralize a counterpart's tendencies to employ questionable or unethical tactics, improving the chances for an integrative (win–win) outcome. The results suggest that while nearly two thirds of participants employed neutralizing behaviors, they used many of these behaviors later in the negotiation process than anticipated and simultaneously alongside questionable or unethical tactics. While we found some evidence that the twelve neutralizing behaviors were viewed differently from questionable or unethical tactics, the expected attenuating effects were not found. The implications of these findings, including opportunities for future research, are discussed.